Dinosaurs-those terrible lizards - Gish, Duane T.; Ross, Marvin (San Diego, Calif. : Creation-Life Publishers, 1977)
Discusses the origins, characteristics, habits, and fate of dinosaurs. Also includes Biblical references to these creatures.
Includes index.
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs